Pendampingan Literasi Membaca Pada Generasi Alpha Di Desa Muneng Kecamatan Purwoasri - Afiyudin, Moh. Sholeh; Fitriani, Rina Amalia; Fransiska Martariyana; Mochamad Nur Risqi; Normala Rista Wike Umami; Ella Yuni Ambarwati (Fakultas Tarbiyah IAIN Kediri, 2024)
Improving reading literacy is an important priority in the development of quality human resources. Muneng Village, Purwoasri Sub-district, Kediri District, faces challenges in improving reading literacy among Alpha Generation children. Data from the Kediri District Education Office in 2023 shows that the village's reading literacy rate is 58%, far below the national average of 75%. One of the main factors influencing the low interest in reading is the excessive use of gadgets, which distracts children from reading books. A Participatory Action Research (PAR) reading literacy mentoring program was implemented to address this problem. The program involves the local community, especially TPQ institutions in Muneng Village, and uses an Active Learning approach to increase children's interest and reading skills. Through interactive activities such as group discussions and role plays, as well as the provision of age-appropriate reading books, the program aims to foster positive reading habits. The results of the program implementation showed an increase in children's interest in reading and literacy skills. The program succeeded in fostering early interest in reading, broadening children's horizons and knowledge, and improving their critical thinking skills and vocabulary. The program made a positive contribution to improving the quality of education in Muneng village and building a sustainable literacy culture. Recommendations for the development of this program include expanding community involvement and adjusting to local needs for more optimal results.